Development of critical thinking as a means of forming STEM competencies - Olha Pylypenko (Academy of Cognitive and Natural Sciences, 2020)
The article analyzes the scientific literature in order to determine different approaches to the interpretation of the concept of "critical thinking", describes its components, discusses the basic concepts, functions of critical thinking in teaching. Critical thinking is presented as one of the main competences of STEM education. The conditions for the development of critical thinking in the process of STEM-learning are determined. Methodical problems are solved, which should help students to develop STEM competences based on the development of their critical thinking.